Design of Appropriate Technology Innovation for Alternators as Power Generating Equipment on Fishery Ship Size < 10 GT - Wijatmika, Wijatmika; Aliredjo, Moch. Subroto; H. Sutisna, Dedy (Agrikan Jurnal Agribisnis Perikanan, 2022)
Designing appropriate technological innovations on the dc motor used to drive the alternator and knowing the performance of the tool. The method used in the research is the experimental design method which includes several stages, namely : (1) requirements analysis, (2) system design, (3) tool making, and (4) tool performance testing. This tool works using DC motor propulsion by rotating the alternator, so that it can rotate to produce an electric voltage which is then stored in an accumulator electrical energy storage cell. Electrical energy stored in batteries (accumulators) can be used to power electronic equipment on fishing vessels >10 GT such as GPS navigation tools, fishfinder lights, simple ones that do not have too much electrical power. Based on the results of the 20-minute test that has been carried out, it can be concluded that this appropriate innovative alternative power generation system can work well at 2000 rpm to 3600 rpm and produce an average voltage of 14.63 volts and an average charging current. - an average of 2.5 amperes.